The labour of reading: Desire, alienation, and Biblical interpretation - Black, Fiona C. (U.S.A, 1999)
What does it mean to work at or labor with the reading of the Bible? How do biblical texts appear when the light under which they are read comes from an unconventional quarter? The labour of reading provides an example of the work of reading biblical texts in new and distinct ways.
Keywords: Bible